The Relationship Between Teacher Leadership and Organizational Happiness of Secondary School Teachers - Töre, Esra; Duman-Şaka, Burçin; Töre, Esra (Tayfun Yagar, 2023)
The study aims to analyze the relationship between teacher leadership and the organizational happiness of secondary school teachers. The research was designed in the relational survey model. The research sample group involves 358 teachers working in the state schools in the Bakirkoy district of Istanbul province. The Teacher Leadership Scale and the Organizational Happiness Scale were used to collect the data. The social sciences statistics program was used in the analysis of the data. It was found that teachers' teacher leadership and organizational happiness levels were high. There was a low level of positive significant relationship between teacher leadership and organizational happiness. and between the positive emotions sub-dimension of organizational happiness and the total score of teacher leadership. However, there was no relationship between the negative emotions sub-dimension of organizational happiness and teacher leadership. It was concluded that teacher leadership significantly positively affects teachers' organizational happiness.
Keywords: Organizational happiness; Secondary school teacher; Teacher leadership